38% Silver Diammine Fluoride Application on Tribal Preschool Children's Caries - Dr Induja Devan (Elsevier, 2023)
Aim or Purpose: The aim of this study to compare the effectiveness of annual, semi-annual, and four times a year application of 38% SDF in arresting active coronal carious lesions on primary teeth of tribal preschool children in India. Materials and Methods: This study is a randomized controlled trial involving tribal preschool children aged 3-6 years visiting primary health Centre in kalpetta India. The participants was randomly assigned to one of three groups: annual, semi-annual, or four times a year application of 38% SDF. The statistical analysis compared the proportion of arrested surfaces at different frequencies using chi-square methods and stratify by tooth type and surface type. Regression analysis models the dependent variable as the percentage of arrested carious lesions per child. The primary outcome measure is the number of arrested cavitated lesions at 12 months follow-up. Secondary outcomes include acceptability of SDF treatment by the child and parents. Results: Overall caries arrest was 84.9%. Biannual (83.2%) and four times application (85.2%) had higher caries arrest than annual application of (79%) with P value of 0.362. There was no statistical significance between the three bgroups. Anterior teeth (86.3%) had higher caries arrest that posterior teeth (83.1%). Conclusions: Caries arrest was achieved in all three frequencies of application with highest in the four times application of SDF annually.